Severe fever with thrombocytopenia syndrome virus infection shapes gut microbiome of the tick vector Haemaphysalis longicornis - Yu Sun; Chen Chen; Chenghong Zeng; Qianfeng Xia; Chuanfei Yuan; Hua Pei (Parasites & Vectors, 2024)
Abstract Background Ticks serve as vectors for a diverse array of pathogens, including viruses responsible for both human and livestock diseases. Symbiotic bacteria hold significant potential for controlling tick-borne disease. However, the alteration of tick gut bacterial community in response to pathogen infection has not been analyzed for any tick-borne viruses. Here, the impact of severe fever with thrombocytopenia syndrome virus (SFTSV) infection on bacterial diversity in the gut of Haemaphysalis longicornis is investigated. Methods Unfed tick females were artificially infected with SFTSV. The gut samples were collected and the genomic DNA was extracted. We then investigated alterations in gut bacterial composition in response to SFTSV infection through 16S rRNA gene sequencing. Results The study found that a reduction in the number of operational taxonomic units (OTUs) in the tick gut following SFTSV infection. However, there were no significant changes in alpha diversity indices upon infection. Four genera, including Corynebacterium, Arthrobacter, Sphingomonas, and Escherichia, were identified as biomarkers for the tick gut without SFTSV infection. Notably, the predicted correlation network indicated that the biomarkers Sphingomonas and Escherichia exhibited positive correlations within the same subcommunity, which was altered upon viral infection. Conclusions These findings revealed that the change in tick gut bacterial composition upon SFTSV infection and could facilitate the discovery new target for tick-borne viral disease control. Graphical Abstract